Basal versus apical dendritic long-term potentiation of commissural afferents to hippocampal CA1: a current-source density study - Kaibara, T (J Neurosci, 1993)
Current-source density analysis was used to estimate the magnitude of the synaptic excitation at the basal and apical dendritic synapses of CA1 following commissural stimulation in the urethane-anesthetized rat, before and after a theta-frequency patterned primed burst tetanus. Stimulation of the contralateral CA3 or the contralateral CA1 stratum oriens excited both the basal and apical dendrites in CA1 about equally. However, primed burst tetanization of the contralateral CA3 or CA1 stratum oriens resulted in significant long-term potentiation (LTP) only at the basal dendrites and not at the apical dendrites. Stimulation of the contralateral CA1 stratum radiatum excited the apical dendrites more than the basal dendrites of CA1, but tetanization of this contralateral site gave little change in the apical or basal dendritic excitation. Tetanization of the contralateral CA1 stratum radiatum after an intraventricular administration of bicuculline, a GABAA antagonist, however, resulted in significant LTP at both the apical and basal dendrites. It was concluded that, in the intact hippocampus in vivo, the threshold for LTP at the commissural apical dendritic synapse was high in comparison to that at the basal dendritic synapse and this high threshold may be partly caused by inhibitory interneurons that predominantly synapsed on the apical dendrites. Thus, the basal and apical dendrites of the CA1 pyramidal cells are not equal in their propensity for long-term plasticity.